2020
DOI: 10.3389/fcell.2020.582247
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Stress Induced DNA Methylation of Monoamine Oxidases Leads to Depressive-Like Behavior

Abstract: Major depressive disorder (MDD) is coming to be the regarded as one of the leading causes for human disabilities. Due to its complicated pathological process, the etiology is still unclear and the treatment is still targeting at the monoamine neurotransmitters. Early life stress has been known as a major cause for MDD, but how early life stress affects adult monoaminergic activity is not clear either. Recently, DNA methylation is considered to be the key mechanism of epigenetics and might play a role in early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 83 publications
1
27
0
Order By: Relevance
“…According to the 5th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) [4], a major depressive episode is defined as a period of 2 weeks or longer during which there is either depressed mood or loss of interest or pleasure (i.e., anhedonia) and four additional symptoms reflecting changes in activity, e.g., psychomotor agitation, retardation or fatigue, change in sleep patterns and suicidality. This disorder is complex, and its etiology, which may include social and psychological factors such as stressful or traumatic events [5,6], inflammation and microbiome [7][8][9], in addition to epigenetic and genetic ones and age-related factors [10][11][12][13], remains unclear to date [14]. Depressive symptoms may be reduced within several weeks after the start of conventional 2 of 16 antidepressants, but treatment resistance concerns one-third of the patients who fail to achieve recovery.…”
Section: Major Depression: Diagnostic Criteria Prevalence and Etiologymentioning
confidence: 99%
“…According to the 5th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) [4], a major depressive episode is defined as a period of 2 weeks or longer during which there is either depressed mood or loss of interest or pleasure (i.e., anhedonia) and four additional symptoms reflecting changes in activity, e.g., psychomotor agitation, retardation or fatigue, change in sleep patterns and suicidality. This disorder is complex, and its etiology, which may include social and psychological factors such as stressful or traumatic events [5,6], inflammation and microbiome [7][8][9], in addition to epigenetic and genetic ones and age-related factors [10][11][12][13], remains unclear to date [14]. Depressive symptoms may be reduced within several weeks after the start of conventional 2 of 16 antidepressants, but treatment resistance concerns one-third of the patients who fail to achieve recovery.…”
Section: Major Depression: Diagnostic Criteria Prevalence and Etiologymentioning
confidence: 99%
“…Due to it being fundamental for cellular processes, our increased understanding of these aspects leads to big consequences for a range of fields. Epigenetics' importance stretches from different fields such as medicine (e.g., , psychology (e.g., Xu et al, 2020), and pedagogy (e.g., Pickersgill, 2020), to ethics (e.g., Taki & de Melo-Martin, 2021) and law (e.g., Dupras et al, 2019), although the knowledge base is not as firmly established for the last three compared to for medicine and psychology. This universal importance is why some biologists talk about a paradigm shift (Gilbert & Epel, 2009).…”
Section: Epigenetics: An Overviewmentioning
confidence: 99%
“…However, epigenetic processes do not stop at birth; rather, they continue to be part of the fundamental cell processes during the rest of the life. In recent years, it has been obvious that epigenetic processes are involved in processes like learning (Collins et al, 2019;Kim & Kaang, 2017;Leighton et al, 2018), stress responses (Cao-Lei et al, 2016;Li et al, 2020;Xu et al, 2020), and during physical activity (Hall et al, 2020;Lindholm et al, 2014;Seaborne et al, 2018). Additionally, individuals suffering from different diseases and disorders present changed epigenetic patterns.…”
Section: Epigenetics: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the onset of major depression are often correlated with stressful events in earlier lives, many studies reported significant correlation between the onset of major depression and the number of traumatic events within 3 months before the onset of the disease. In addition, stress can happen very long ago, for example, early life stress can induce emotional depression in adult lives ( 3 ). This means stress can induce long term changes in the body to induce emotional disorders.…”
mentioning
confidence: 99%